2011
DOI: 10.2169/internalmedicine.50.5640
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Barometric Pressure in Patients with Migraine Headache

Abstract: Objective Barometric pressure has been reported as a triggering and exacerbating factor in migraine headaches, although there are few reports concerning the association of weather change and migraine headache. The relationship between barometric pressure changes and migraine headaches was prospectively examined. Methods A total of 28 migraine patients who lived within 10 km of the Utsunomiya Local Meteorological Observatory kept a headache diary throughout the year. Daily and monthly mean barometric pressure d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 23 publications
(23 reference statements)
1
46
0
Order By: Relevance
“…Prince et al [38] and Hoffmann et al [36] found a relationship between low ambient temperature and high relative humidity and the incidence of migraine. Kimoto et al observed a correlation between decreases in atmospheric pressure and increases in migraine frequency, which underlines the previous results as low atmospheric pressure (or its decrease) is commonly associated with low temperature and high humidity due to precipitation [37]. Importantly, the study by Hoffmann et al also revealed that only a subgroup of migraineurs seem to be weather-sensitive, providing a possible explanation as to why clinical studies have substantial difficulties in proving such a common patient perception [36].…”
Section: Weathersupporting
confidence: 76%
“…Prince et al [38] and Hoffmann et al [36] found a relationship between low ambient temperature and high relative humidity and the incidence of migraine. Kimoto et al observed a correlation between decreases in atmospheric pressure and increases in migraine frequency, which underlines the previous results as low atmospheric pressure (or its decrease) is commonly associated with low temperature and high humidity due to precipitation [37]. Importantly, the study by Hoffmann et al also revealed that only a subgroup of migraineurs seem to be weather-sensitive, providing a possible explanation as to why clinical studies have substantial difficulties in proving such a common patient perception [36].…”
Section: Weathersupporting
confidence: 76%
“…For example, a low barometric pressure increases the risk for suicide attempts in Finland, exacerbates depression‐like behavior in rats, and potentiates neuropathic pain in guinea pigs . In a small prospective study from Japan, the frequency of migraine headaches was higher after a sudden decrease in atmospheric pressure . Although the underlying mechanisms are still a matter of speculation, lowering the atmospheric pressure in an air pressure chamber increases the neuronal activity in rats .…”
Section: Discussionmentioning
confidence: 99%
“…A few other studies have shown weather and barometric change as trigger factors. [2324] Head movement has not been cited as a common migraine trigger factor. [25] Head and neck movement could be categorized as cervical triggers, which increase the peripheral sensitization from the cervical afferents.…”
Section: Discussionmentioning
confidence: 99%